The Role of Lay Workers in Providing Psychosocial Support for Cancer Patients - Hermawan, Stepanus Maman; Wihardja, Hany (Indonesian Journal of Nursing and Health Sciences, 2025)
Psychosocial support plays an important role in improving the quality of life of cancer patients, especially through assistance by lay workers. This study aimed to explore lay workers' experiences in providing psychosocial support to cancer patients. This study used a qualitative approach with an in-depth interview method with 14 participants selected by purposive sampling. Participants were lay workers who had attended basic and advanced palliative training, as well as cancer awareness guidance, and had experience in providing palliative assistance to cancer patients for more than one year. The data collection technique used was deep interviews, which were conducted directly with participants. The data collected were thematically analysed through interview transcription, coding, pattern identification, theme review, and research report preparation. The research identified four main themes: (1) forms of psychosocial mentoring, (2) challenges in mentoring, (3) support and collaboration during mentoring, and (4) strategies and development of psychosocial mentoring. Lay workers used various approaches, including emotional presence, relaxation techniques, moral support, and education to help patients overcome anxiety, fear, and loneliness. The main challenges faced included difficulties in building patient openness, limited lay worker skills, and lack of family support. Support from health workers and collaboration with families play a role in optimizing assistance. Further training is needed to improve lay workers' skills in dealing with complex psychological problems. A more personalized, empathy-based and integrated approach can strengthen support and increase the effectiveness of psychosocial assistance.